2019
DOI: 10.1021/acs.langmuir.9b01215
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Confined Liquids: Challenges and Perspectives for the X-ray Surface Forces Apparatus

Abstract: The molecular-scale structure and dynamics of confined liquids has increasingly gained relevance for applications in nanotechnology. Thus, a detailed knowledge of the structure of confined liquids on molecular length scales is of great interest for fundamental and applied sciences. To study confined structures under dynamic conditions, we constructed an in situ X-ray surface forces apparatus (X-SFA). This novel device can create a precisely controlled slit-pore confinement down to dimensions on the 10 nm scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 140 publications
0
24
0
Order By: Relevance
“…The surface force apparatus, atomic force microscopy as well as scanning tunneling microscopy are some of the most promising techniques to investigate changes in the slip length and in the viscosity under confinement. 25,46 Additionally, measurements of the slip length in nanotubes using optical microscopy have shown that water essentially does not slip inside BN nanotubes, whereas it does slip inside carbon nanotubes, the slip length being larger in nanotubes with smaller radii. 8 In the carbon nanotubes with the lowest curvature (100 nm in diameter), the reported slip length of about 23 nm compares favorably with our predicted value for graphene, 19.6 ± 1.9 nm.…”
mentioning
confidence: 99%
“…The surface force apparatus, atomic force microscopy as well as scanning tunneling microscopy are some of the most promising techniques to investigate changes in the slip length and in the viscosity under confinement. 25,46 Additionally, measurements of the slip length in nanotubes using optical microscopy have shown that water essentially does not slip inside BN nanotubes, whereas it does slip inside carbon nanotubes, the slip length being larger in nanotubes with smaller radii. 8 In the carbon nanotubes with the lowest curvature (100 nm in diameter), the reported slip length of about 23 nm compares favorably with our predicted value for graphene, 19.6 ± 1.9 nm.…”
mentioning
confidence: 99%
“…Surface X-ray scattering is capable of resolving the arrangement of solvent molecules and ions near electrode surfaces with the desired molecular resolution, in particular when combined with atomic scale modeling; it has recently also been employed for confined environments. 83 However, this technique necessitates atomically smooth surfaces; thus, model systems are required such as single crystalline metal oxides surfaces. For example, Harmon et al 84 and Steinru ¨ck et al 67 have utilized sapphire substrates to investigate the arrangement of water molecules within the EDL and lithium-ion battery electrolytes, respectively.…”
Section: Membrane Foulingmentioning
confidence: 99%
“…Two-dimensional single chains, monodisperse solutions and melts were subjects of many experimental and theoretical studies, and thus, their structure and dynamics are well known. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] On the other hand, the number of theoretical works on the structure of polydisperse polymer systems is rather limited. [20][21][22][23][24] Nevertheless macromolecules obtained in real experiments, i.e., during the polymerization processes are always polydisperse.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] The structure of two-dimensional polymer systems are generally still unclear especially when one asks if they obey the Gaussian statistics. [12][13][14][15][16][17][18][19] Strictly two-dimensional polydisperse macromolecular systems have also been studied [22,23] and a different scaling behavior has been shown at high polymer concentrations, i.e., a considerably higher exponent 𝜈 was found for longer chains which has been interpreted as indicating that longer chains are likely to adopt more extended conformations. The dynamics of polydisperse polymer melts were studied by means of dissipative particle dynamics.…”
Section: Introductionmentioning
confidence: 99%